Proceedings of the 12th International Conference on Hypernuclear and Strange Particle Physics (HYP2015) 2017
DOI: 10.7566/jpscp.17.062005
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Observables in γpK+ + Λ and K+ + Σ0 Using Circularly Polarized Photons on a Polarized Frozen Spin Target

Abstract: The search for undiscovered excited states of the nucleon continues to be a focus of experiments at the Thomas Jefferson National Accelerator Facility (JLab). A large effort using the CEBAF Large Acceptance Spectrometer (CLAS) detector has provided the database, which will allow nearly modelindependent partial wave analyses (PWA) to be carried out in the search for such states. Polarization observables play a crucial role in the effort, as they are essential in disentangling the contributing resonant and non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The magnitude of φ ′ was also consistent with the CUA result [62]. CUA extracted the angle by studying the raw target asymmetry for the reaction γp → π + X.…”
Section: Target Polarizationsupporting
confidence: 83%
See 2 more Smart Citations
“…The magnitude of φ ′ was also consistent with the CUA result [62]. CUA extracted the angle by studying the raw target asymmetry for the reaction γp → π + X.…”
Section: Target Polarizationsupporting
confidence: 83%
“…Some quick fixes were carried out in order to resume data taking at the earliest possible. The quality of the data following the quench was studied in [62]. It was observed that the data taken after the quench had more background rendering the analysis more challenging.…”
Section: The Frost Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…The s-channel diagram of the single-pion photoproduction process with baryon excited states as the intermediate product. This figure is from[17].…”
mentioning
confidence: 99%